Institutionalising dialogue in Rwanda through innovation platforms - Schut, Marc (2016)
A platform of farmers, retailers and service providers,civil society organisations, NGOs, government officials, and researchers improves livelihoods in Rwanda. Through interaction and collaboration, these groups experiment with various technological and institutional innovations, thereby tackling local agricultural challenges. This experience illustrates the importance of institutionalising a space where knowledge can be co-created.